Developing and implementing a multi-modality imaging optimization study in paediatric radiology: Experience and recommendations from an IAEA coordinated research project. (February 2021) - Delis, H.; Homolka, P.; Chapple, C.L.; Costa, P.R.; Attalla, E.; Lubis, L.E.; Sackey, T.A.; Fahey, F.; Lassmann, M.; Poli, G.L.
Highlights: There are practical issues in collecting and interpreting data for optimization. Collection of reliable data for optimization requires a well-structured methodology. External advice or collaborative activities between centers can maximize benefits of the process. Abstract: Optimization of imaging examinations is a key requirement of both the International and European Basic Safety Standards, and the focus of much international activity. Although methodologies are well established in principle, there continues to be a variety of practical issues both in collecting and interpreting dose and image quality data and in making successful interventions to optimize exposures. A Coordinated Research Project, involving institutes from ten different countries, was established by the IAEA to assess the efficacy of recommended optimization methodologies in the field of paediatric radiology and to derive practical guidance on their implementation. The steps followed in this process were identification of the imaging process to be investigated (abdomen and chest x-rays, micturating cysto-urethrograms, and brain & thorax CT scans); collection of dose and image quality data; evaluation and comparison of the data between institutes and to standards; identification and implementation of interventions for optimization; and re-evaluation of dose and image quality parameters. The project succeeded both in achieving effective interventions for optimization of specific imaging tasks in individual institutes and in identifying key issues with potential to handicap this process. The main area in which problems were encountered was in the collation of reliable dose and image quality data. The reasons for this were explored and a series of recommendations have been made, summarized into 'ten practical tips' for optimization to assist institutes, particularly those in the early stages of addressing optimization issues.